Eliadowskie zegary czasu mitologicznych i religijnych wierzeń oraz praktyk - Drozdowicz , Zbigniew (Humaniora. Czasopismo Internetowe, 2022)
In practice, every researcher of religion faces the issue of such description and explanation of various beliefs and the related practices which have to be localized in a specific place and time. On the otherhand, those of them who make the attempt to present them in a holistic manner must construct such a time clock which might be applied towards those who which they see as historically most significant. Such a scholar was Mircea Eliade. Similar to many other researchers of these beliefs and practices he had faced the problem of finding such a common “denominator” which enables us to present not only what is dividing them but also what joins them. In the latter case it had been personified by the religious persona (homo religiosus), who independently from place and time could achieve a state of such perfection which would allow eternal existence. Its main issue is based on the fact that he can only realize this desire in a specific place and time, and the latter foten becomes a serious threat to him. In Eliade’s view it is the clash between the sacred and the profane. The problem he tried to solve during his many years of research work was based not just on how to show the historical functioning of these two worlds but also how to explain the fact that in Western culture the first one is more and more giving up the field to the latter one. He had used not one but two time clocks – the first one is measuring the sacred time and the other the secular one. It is however discussable in what extent these measurements are accurate or (what is basically the same issue) if those clocks are well constructed.